Biofabrication Using Pyrrole Electropolymerization for the Immobilization of Glucose Oxidase and Lactate Oxidase on Implanted Microfabricated Biotransducers - Christian N. Kotanen; Olukayode Karunwi; Anthony Guiseppi-Elie (Bioengineering, 2014)
The dual responsive Electrochemical Cell-on-a-Chip Microdisc Electrode Array (ECC MDEA 5037) is a recently developed electrochemical transducer for use in a wireless, implantable biosensor system for the continuous measurement of interstitial glucose and lactate. Fabrication of the biorecognition membrane via pyrrole electropolymerization and both in vitro and in vivo characterization of the resulting biotransducer is described. The influence of EDC-NHS covalent conjugation of glucose oxidase with 4-(3-pyrrolyl) butyric acid (monomerization) and with 4-sulfobenzoic acid (sulfonization) on biosensor performance was examined. As the extent of enzyme conjugation was increased sensitivity decreased for monomerized enzymes but increased for sulfonized enzymes. Implanted biotransducers were examined in a Sprague-Dawley rat hemorrhage model. Resection after 4 h and subsequent in vitro re-characterization showed a decreased sensitivity from 0.68 (±0.40) to 0.22 (±0.17) µA·cm−2·mM−1, an increase in the limit of detection from 0.05 (±0.03) to 0.27 (±0.27) mM and a six-fold increase in the response time from 41 (±18) to 244 (±193) s. This evidence reconfirms the importance of biofouling at the bio-abio interface and the need for mitigation strategies to address the foreign body response.